DESIGN AND FORECASTING IN MODERN PEDAGOGY - Teshaboyev, Akramjon; Doncheva, Julia (International Journal of Formal Education, 2025)
The significance of strategic planning and pedagogical forecasting in education is examined in this article. Improving the educational system’s effectiveness is thought to be crucial for society’s steady progress. A crucial instrument for organising the educational process and facilitating productive teacher-student interaction is pedagogical design. The article examines approaches to pedagogical process design and forecasting and their effects on educational outcomes and quality. It also emphasises how important project-based learning technologies and pedagogical design are to the teaching process.